CEFTA as a Proven Path to Accession to the European Union - Dziuba, Radosław (Comparative Economic Research. Central and Eastern Europe, 2013)
At the beginning of the 1990s Poland, like the majority of the Central and East European countries (CEECs) undergoing transformations, overcame its initial distrust and began to recognize that the only path to regional stability and national economic growth was economic integration. The Central and Eastern European Free Trade Agreement (CEFTA), signed by the Czech Republic, Hungary, Poland, and Slovakia on 21 December 1992 in Cracow, provided for the elimination of a number of trade barriers and the growth in commercial exchanges between the signatory nations, aimed at facilitating their integration with the European Union at a later stage. This article constitutes an attempt to assess the main effects of the implementation of CEFTA on the functioning of its member states as well as their further integration as Member States of the EU. It also presents the main provisions of the modernized CEFTA 2006, and the current problems related to implementation of the agreement. It also discusses the opportunities and prospects for Croatia, as a former CEFTA member state, upon its scheduled accession to the EU in July 2013. This article is intended as an introduction to further and deeper analysis in this area.